2017
DOI: 10.1371/journal.pone.0169318
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Neck/Shoulder Perfusion Characteristics and Pain Symptoms of the Female Office Workers with Sedentary Lifestyle

Abstract: AimModern office workers are often impacted by chronic neck/shoulder pain. Most of the previous studies which investigated the relationship of the occupational factors and musculoskeletal symptoms had adopted questionnaire survey. In this study the microcirculatory characteristics and perceived symptoms in neck/shoulder region were compared among office workers with sedentary lifestyle.MethodsThirty-seven female office workers were recruited in this study. Microcirculatory flow in neck/shoulder region characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…[14,15] Recent papers have also shown that exposure to computers and mobile phones will increase the risk of MSDs. [3,16] The impact of MSDs can be reduced by the implementation of prevention programs, [17] including ergonomic interventions [18] and physical activity. [19,20] However, the use of mechanical supports and other physical interventions are ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Recent papers have also shown that exposure to computers and mobile phones will increase the risk of MSDs. [3,16] The impact of MSDs can be reduced by the implementation of prevention programs, [17] including ergonomic interventions [18] and physical activity. [19,20] However, the use of mechanical supports and other physical interventions are ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…according to studies conducted on 513 office workers, 50.5% of them reported shoulder pain [37]. in this group of patients, the pain correlates to age and work experience [38]. it should be noted that, in most cases, their pain was non-specific [26].…”
Section: Epidemiologymentioning
confidence: 99%
“…Several studies have simultaneously addressed all the involving factors related to UCS by applying exercise therapy. However, scarce research has focused on some separate areas of the upper body including the neck or shoulder among o ce workers (20,32,35,(42)(43)(44)(45). According to (46), the world is currently experiencing an extraordinary, life-altering challenge due to social-distancing and home quarantine recommended by the World Health Organization in order to minimize the speed of the coronavirus disease (COVID-19).…”
Section: Introductionmentioning
confidence: 99%